PENGARUH RASIO KEUANGAN TERHADAP PERUBAHAN LABA PADA PERUSAHAAN YANG GO PUBLIC DI BURSA EFEK INDONESIA - Abidin, Zainal (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
Profit growth is the information that gives an overview of the results of operations and prospects of the companys financial condition in the future. To know good or bad financial condition of a company can use financial ratio analysis. The sample in this study are 9 manufacturing companies listed on the Indonesia Stock Exchange. Financial ratios used are current ratio, debt to equity, total asset turnover, return on equity, return on assets and gross profit margin. The analysis technique used is multiple linear regression analysis, F test and t test. From the results of linear regression model known the existing of influence of current ratio, debt to equity, total asset turnover, return on equity, return on assets and gross profit margin due to changes of earnings because coefficient of regression â  0. Based on the results of the F test is known that the sig <0.05 so that the conclusion can be drawn that the financial ratios consists of current ratio, debt to equity, total asset turnover, return on equity, return on assets and gross profit margins simultaneously have influence to the change of earning. From the t test results known that the current ratio, return on equity, and return on assets partially have influence to the changes of earning in the value of sig <0.05. While the independent variable debt to equity, total asset turnover and gross profit margin partially have no influence to the changes of earning in the value of sig > 0.05.Keywords : changes of earnings, financial report, financial ratios